GANDHARWA WEDA: MEMAHAMI PRINSIP KERJA KREATIF MPU KANWA - I Wayan Suka Yasa (DHARMASMRTI: Jurnal Ilmu Agama dan Kebudayaan, 2018)
The object of this writing is one stanza of the Kakawin Arjuna Wiwaha. The text is reviewed to discover the worldview and creative working principle of the poet, Mpu Kanwa. In this context the analysis is based on rasa (Indian and Old-Javanese aesthetics) and semiotic theory. It is understood that purwa karma, i.e. yoga is the work of nobleness. This is the view of the world of Mpu Kanwa. The creative work is based on empowerment in an integrated and the focus between power of taste, power of mind, and power of desire. The three creative forces that gave birth to sense of art (taksu) which in the process of sustainable by itself has made someone as the center of dignity for the community.